The Problematic of Determining Competencies Concept Between Behavioral and Performance Approaches - Abulkacem, Hamdi (Journal of Excellence for Economics and Management Research, 2017)
The purpose of this article was to study different researches which addressed to human resource competencies topic, and which mainly focused on values dimension. We’ve tried to demystify two approaches « Behavioral and francophone »; the first has concentrated on behavior and different underlying characteristics of competencies (especially values. The second (Francophone) has focused on the outputs of performance which neglected totally the behavior during performance. So we found that francophone approach has not concentrated on values, because it was based on the explicit characteristics and neglected the implicit ones, while it normally based on all components that including values which considered as the main behavior determinant factor.